2017
DOI: 10.1007/s00382-017-3649-2
|View full text |Cite
|
Sign up to set email alerts
|

Decadal prediction of the North Atlantic subpolar gyre in the HiGEM high-resolution climate model

Abstract: These results support an important role for the ocean in driving past changes in the North Atlantic region, and suggest that these changes were predictable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 68 publications
6
32
0
Order By: Relevance
“…Recently, Hermanson et al (2014) and Robson et al (2016Robson et al ( , 2017 analyzed the outputs of coupled climate models and identified a new cooling and freshening period from the mid-2000s. Their results coincide with observations: Johnson et al (2016) documented an SPNA region cooler in 2014 than in 1993-2014 climatology, and this cooling intensified in 2015 and 2016 Loder, 2016, 2017).…”
Section: Along With a Schematic View Of The Upper Intermediate And mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hermanson et al (2014) and Robson et al (2016Robson et al ( , 2017 analyzed the outputs of coupled climate models and identified a new cooling and freshening period from the mid-2000s. Their results coincide with observations: Johnson et al (2016) documented an SPNA region cooler in 2014 than in 1993-2014 climatology, and this cooling intensified in 2015 and 2016 Loder, 2016, 2017).…”
Section: Along With a Schematic View Of The Upper Intermediate And mentioning
confidence: 99%
“…As shown by Robson et al (2016), the SPNA started a new long-term cooling period since the mid-2000s. By analyzing the outputs of coupled climate models, Robson et al (2017) Jan 2013 argued that this new cooling period is led by the reduced ocean heat transport convergence resulting from a long-term slowdown of the AMOC. Within this long-term cooling period, we will focus hereafter on the pronounced heat content drop that happened between 2013 and 2014.…”
Section: Negative Anomalies Of θ and S In Surface Intermediate Layersmentioning
confidence: 99%
“…At the same time the deep water formation that takes place in the North Atlantic, renders it a critical region for changes in the Atlantic meridional overturning circulation (AMOC; Hátún et al, 2005). The North Atlantic is a region where skillful predictions of up to a decade can be obtained, namely, in the NASPG as seen in previous studies using various different decadal prediction systems/setups (e.g., Brune et al, 2018;Matei et al, 2012;Polkova et al, 2015;Robson et al, 2018;Smith et al, 2010). However, as indicated by Barrier et al (2015, and references therein) using the Nucleus for European Modelling of the Ocean (NEMO) system, the prediction skill in the NASPG on decadal time scales is high in the western part of the gyre and low in the eastern part and thus the spatial patterns need to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…The North Atlantic subpolar gyre region is one of the most predictable marine regions worldwide (Matei et al., ; Meehl et al., ), and therefore opens the door to forecasting this distribution. In particular, the switch from one marine climatic regime to another could be a key starting point: modelling studies have shown the ability to retrospectively predict the mid‐1990s contraction of the SPG (Msadek et al., ; Wouters, Hazeleger, Drijfhout, van Oldenborgh, & Guemas, ), and the associated increase in the upper 500 m heat content up to 5 years in advance (Robson, Polo, Hodson, Stevens, & Shaffrey, ). Consequently, the onset of warmer and more saline conditions in the spawning region of blue whiting and an expanded spawning distribution of this species could potentially be predicted.…”
Section: Resultsmentioning
confidence: 99%